Implementation of Expert System for Early Detection of Breast Cancer With Web-Based Methods Chaining Forward: Implementation of Expert System for Early Detection of Breast Cancer With Web-Based Methods Chaining Forward - Diana Caniago; Septi Andryana; Aris Gunaryati (Jurnal Mantik, 2020)
Breast cancer will be easier to overcome if it is known as early as possible to the importance of self-awareness to perform a routine inspection of BSE. The study presented aims to design a web-based application in the health field in the early detection of breast cancer. Penelian expert system method on this is to use forward chaining to represents the rule and reasoning into a coherent system based on physical symptoms entered. In this system also gets a percentage probability of 72.7%, so it can be quite good. In addition the system can produce two outputs in the form of possibility, the output is both benign and malignant.